MicroPop: Modelling microbial populations and communities in R. Issue 2 (14th September 2017) - Kettle, Helen; Holtrop, Grietje; Louis, Petra; Flint, Harry J.
Abstract: Microbial communities perform highly dynamic and complex ecosystem functions that impact plants, animals and humans. Here we present an R‐package, microPop, which is a dynamic model based on a functional representation of different microbiota. microPop simulates the dynamics and interactions of microbial populations by solving a system of ordinary differential equations that are constructed automatically based on a description of the system. Data frames for a number of microbial functional groups (MFG) and default functions for rates of microbial growth, resource uptake, metabolite production are provided but can be modified or replaced by the user. microPop can simulate growth in a single compartment (e.g. bio‐reactor) or "compartments" in series (e.g. human colon) or in a simple 1D application (e.g. phytoplankton in a water column). Furthermore, an MFG may contain multiple strains in order to study adaptation and diversity or parameter uncertainty. Also simple interactions between viruses (bacteriophages) and bacteria can be included in microPop . microPop is hosted on CRAN and can be installed directly from within R. This paper describes version 1.3 of microPop . The code is also hosted on GitHub for future development (https://github.com/HelenKettle/microPop ).